Mediating Effects of Enforcement on Public Procurement Guidelines' Compliance Barriers and Cost Performance of Construction Projects in Nigerian Federal Universities: A Process Macro Approach - Zadawa, Abdullahi Nafu; Hussin, Abdul Aziz; Osmadi, Atasya (Penerbit Universiti Sains Malaysia, 2018)
"Mediation analysis" is considered as an important research concept in construction research clusters. In this study, we tested the mediation effects' of enforcement as a compliance mechanism on inﬂuencing projects' award considered as public procurement guidelines' (PPGs) compliance barriers that affect the cost performance of construction projects. Compliance with PPGs provided within the context of the Public Procurement Act (PPA) 2007 in Nigeria has been a subject of debate. Data for this study was collected from the procurement stakeholders and construction project parties of nine randomly selected Nigerian federal universities using survey questionnaires. They included project clients, contractors registered with the procurement entities, project management consultants and professional consultants selected using the stratifed proportionate random sampling method. The data collected was analysed and tested for mediation effects with Process Macro. The results obtained indicated that enforcement as a compliance mechanism has mediated the large negative effects of inﬂuencing project award as PPGs' compliance barriers that affects construction project cost performance. Thus, the study concluded that inﬂuencing projects award were identifed as one of the major PPGs' compliance barriers affecting the cost performance of construction projects in Nigeria. In addition, enforcement was tested and verifed as an effective mediator that mitigates the effects of the inﬂuencing projects award on construction project cost performance. The study recommends the prompt implementation of enforcement actions in the form of penalties and strict measures against any defaulting stakeholders and construction project parties. Actions to establish the National Council of Public Procurement (NCPP) as provided by the PPA 2007 are also recommended to ensure practicable enforcement actions